CBT repackaged or a novel treatment? The Lightning Process compared with UK specialist medical care for paediatric Chronic Fatigue Syndrome. Issue 2 (3rd April 2021) - Anderson, Emma C.; Loades, Maria; Starbuck, Jennifer; Parker, Phil; Finch, Fiona; Barnes, Rebecca; Beasant, Lucy; Crawley, Esther
ABSTRACT: Rationale: UK specialist medical care (SMC) for paediatric Chronic Fatigue Syndrome (CFS/ME) includes behavioural approaches (Graded Exercise Therapy; Activity Management) and Cognitive Behavioural Therapy for fatigue (CBT-F). Treatment is suboptimal with a third of children not recovering after 6 months of SMC. Many families seek alternative treatments at personal cost, including the Lightning Process (LP). Evidence shows LP can improve patient outcomes, though this intervention is not widely known/understood. Objectives: To describe LP in comparison with SMC approaches in order to identify distinct elements, inform clinicians about treatment options, and generate hypotheses around effectiveness. Methods: Theoretical comparison including stakeholder consultation. Results: While overlaps with SMC approaches were identified, and CBT-F in particular, distinct elements of LP were its focus on language style, neurophysiological rationale, affective/physiological change technique and mode of delivery. Conclusion: This theoretical comparison identified distinct elements of LP which could be explored in future interventions or research aiming to improve clinical outcomes for children with CFS/ME, and informs clinicians about treatment options available for families.